Kandungan Glukosa Karetonoid dan Biomasa Alang-Alang yang Tumbuh di Daerah Padang Terbuka Kabupaten Blora dan Kabupaten Ungaran - Fujianto, Zelly; Prihastanti, Erma; Haryanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
The Objective of this research was to analyse glucose, carotenoid, and biomass of Alang-alang (Imperata cylindrical L. Beauv) that grew at open field area on the both Recidence of Blora and Ungaran. Completely Randomized Design was applied in this research that using single factor ( different level of place ) with 3 times replication. Data was analysed by T test with 99 % and 95%Â  significant level. The parameter was observed include environmental factors, content of glucose and carotenoid, biomass of Alang-alang. The Result showed that Blora Recidence have higher temperature and light intensity. However, the moisture and rainfall intensity is low. Alang-alang that grow in Blora recidence have higher content of glucose and carotenoid, but the its biomass is low. Â  Keywords : environmental factors, glucose, carotenoid, the biomass of Alang-alang